Structural Development, Deposition Model and Petroleum System of Paleogene Carbonate of the Engkabang-Karap Anticline, Onshore Sarawak - John Jong; Frank Kessler; Steve Noon; Tran Quoc Tan (Ikatan Ahli Geologi Indonesia, 2016)
To further investigate the hydrocarbon potential of the 400 km2 large Eocene - Oligocene carbonate body of the Engkabang-Karap Anticline, onshore Sarawak, high-resolution 2D seismic data, aero-gravity and magnetics were acquired by JX Nippon in 2009 and 2010. Interpretation of the latter confirmed the existence of a large carbonate-cored anticline, previously drilled by Shell in 1959-1960 and proving sub-economic gas in a massive 272m section of tightly cemented and dolomitized limestone, with little or no matrix porosity/permeability retained.Recent drilling results of Engkabang West-1 by JX Nippon confirmed the presence of gas in tight carbonate reservoirs, consisting of mainly mudstone and wackestone, but DST flow rates proved to be un-economic. The latest biostratigraphic analyses of the Engkabang wells indicate the presence of a number of key stratal events related to regional unconformities and hiatuses, suggesting that the basin ramp area saw periods of compression, inversion and/or uplift. The new seismic data indicate significant structural deformation, including strike-slip tectonism and local overthrusting, not seen on older seismic, nor noticed from the interpretation of surface geology. There is also seismic evidence of a low-angle detachment plane, linked to a zone of increased tectonism commonly referred to as the Baram Line. Other than in the nearby Lambir Hills, there is hardly any visible sign of major deformation on the surface, whilst biostratigraphic data of the Engkabang wells suggest the last folding event occurred during the Pliocene. Associated with elements of compressive folding, thrusting and strike-slip movements, the study area seemed to have undergone strong tectonic stresses caused by movements along the nearby Baram Line and Belait Wrench system.This resulted in active mud volcanism, with the active Karap mud volcano located to the southwest of Marudi Township. Post-folding, peneplanation truncated the anticline, followed by a cover of Quaternary alluvial deposits. The proposed structural model, an overthrust system rooted in a low-angle detachment plane, explains the occurrences of both shallow oil and deep gas, including mud volcanism. This trapping mechanism may also be present in other areas of onshore Sarawak and can be considered as a new hydrocarbon play. Although the petroleum system is relatively well-established with significant potential upside, technical challenges remain to further derisk the carbonate play. The tight reservoir facies encountered in both wells suggest well-developed fracture systems will be needed to improve flow rates, but fracture orientation can only be mapped with properly designed 3D seismic coverage.